Mild to Severe Depressive Symptoms in Elderly Stroke Survivors and Its Associated Factors: Evidence From a Cross-Sectional Study in Zhejiang Province, China - Wang, Xinyi; Li, Fudong; Zhang, Tao; He, Fan; Lin, Junfen; Zhai, Yujia; Yu, Min (Frontiers in Psychiatry, 2021)
Objectives: To explore the prevalence of depressive symptom in elderly stroke survivors and its associated factors. Methods: We did data analyses for 335 elders with stroke history. Data were collected in a survey conducted between 2014 and 2015, among permanent residents aged 60 and older in Zhejiang Province, China. Prevalence of depressive symptom among stroke survivors were calculated, univariate analyses and multilevel logistic regression were used to explore its associated factors. Results: Prevalence of depressive symptom was 22.09% (95%CI: 17.65%-26.53%) in elders with stroke history, more than twice compared to their counterparts not suffering stroke (9.77%, P<0.001). In multilevel logistic regression, we found that elderly stroke survivors who were illiterate (OR=2.33, p=0.008), had limitation in activities of daily living (OR=3.04, p=0.001) were more likely to be present with depressive symptom, respectively, while those with more fresh vegetable consumption were at lower odds (OR=0.82, p=0.047). Conclusions: Prevalence of depressive symptom was high in elderly stroke survivors. Targeted screening are especially needed for those being illiterate, disabled in activities of daily living and having little consumption of fresh vegetable. The association between fresh vegetable consumption and depressive symptom in stroke patients calls for further research.